2002
DOI: 10.1093/molehr/8.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase (MMP)-2 and MMP-9 activities in human seminal plasma

Abstract: We report on the existence of two kinds of matrix metalloproteinases (MMPs), MMP-2 and MMP-9, in human seminal plasma. Partial purification of the proteinases was achieved by two steps, consisting of chromatography on a gel-filtration column and then on a gelatin affinity column. Proteinase activities in the chromatography extracts were shown to hydrolyse a fluorescent substrate specific to MMPs (Dnp-Pro-Leu-Gly-Leu-Trp-Ala-D-Arg-NH2). The proteinases were detected using gelatin-zymography, but were not detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
8

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 18 publications
2
60
0
8
Order By: Relevance
“…Based on previous reports (Metayer et al 2002;Shimokawa et al 2002;McCauley et al 2001;Tentes et al 2007), the bands with 225, 78 and 66 kDa correspond to dimer-MMP-9, proMMP-2 and active MMP-2. The variation in molecular weights (by 10 to 15 kDa) of gelatinases of different origins can be result of different glycosylation (Metayer et al 2002).…”
Section: +mentioning
confidence: 61%
See 2 more Smart Citations
“…Based on previous reports (Metayer et al 2002;Shimokawa et al 2002;McCauley et al 2001;Tentes et al 2007), the bands with 225, 78 and 66 kDa correspond to dimer-MMP-9, proMMP-2 and active MMP-2. The variation in molecular weights (by 10 to 15 kDa) of gelatinases of different origins can be result of different glycosylation (Metayer et al 2002).…”
Section: +mentioning
confidence: 61%
“…The variation in molecular weights (by 10 to 15 kDa) of gelatinases of different origins can be result of different glycosylation (Metayer et al 2002). Bands with lower molecular weights can represent the degradation products of metalloproteases with enzymatically active domain (Shimokawa et al 2002). This can be explained because both MMP-2 and MMP-9 have gelatin binding domains in their catalytic domains (Banyai et al 1994).…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggested that increasing enzymatic activity of MMP-2 might play a role in male infertility. Shimokawa et al showed that there is an active-form and a pro-form of Matrix Metalloproteinase-2 and its degradation products are present in human seminal plasma (12). In vitro studies have shown that the Follicle Stimulating Hormone (FSH) increases expression of MMP-2 in testicular sertoli cells (11).…”
Section: Discussionmentioning
confidence: 99%
“…Gelatinases are one of the subtypes of matrix metalloproteinases and includes matrix metalloproteinases 2 and 9 (collagenases A and B with molecular weight of 72 and 92 kD, respectively). These enzymes usually degrade gelatin and collagen type 4 (12)(13)(14). Matrix Metalloproteinase-2 is synthesized and secreted as a zymogen so the activation of MMP-2 is an important step in controlling its activity.…”
Section: Introductionmentioning
confidence: 99%